HAT SEBAGAI MODALITAS KEPERAWATAN PADA LASERASI SCALP DI IGD - Lale Wisnu Andrayani (Jurnal Kesehatan Prima, 2015)
Abstract: Background: "Saving lives" based on the degree of acuteness is a general principle in determining the priority of patients with acute condition, but it is not the only cause of the complexity of the situation in the emergency department (ED). Patients with non-emergency or non-urgent condition in large amounts can also contribute to an increase in overcrowded conditions, one of which is a laceration of the scalp (scalp). Closure of the wound on the scalp through invasive procedures have several limitations including a relatively long time and is often reported to be a painful procedure that can be a traumatic experience, especially for children. One modality that can be used as an alternative is apposition Hair Technique (HAT). Methods:  Identification of relevant Hair apposition Technique literature in the form of articles and research. Results: Three (3) among the reviewed research articles (original research) was a randomized controlled trial (RCT). In general, the third research found that HAT procedure seems more advantageous than standard wound closure techniques in  pain less and scarring, minimal complications and a faster procedure than standard suturing techniques. However, two of the research have differences results in terms of patient satisfaction related process of wound healing, infection and bleeding or wound breakdown (open wound back). One other study also reported advantage of a higher cost effective in HAT compared to standard wound closure procedures. In addition, application of HAT by ER nurse seems to be equally good results with application by doctor but with a more sympathetic approach to care and focus on the patient .Conclusion: Hair Apposition Technique can provide greater benefits in achieving the main goal of wound closure and its convenient and cost effectively effects allows application of HAT by Emergency Room (ER) nurse.